صورة الأب ودورها في ظهور الجنوح لدى المراهق - بيروق, هناء نور الهدى (Changement Social; No 05 (2018): revue change social, 2018)
للأسرة وظيفة هامة في المجتمع وتتمثل في تنشئة الأبناء وغرس القيم الأخلاقية والفضائل الحميدة فيهم  وهذا ما يترجم من خلال تكامل أدوار أفرادها وتفاعلهم فيما بينهم خاصة الوالدين، إلا أنه بتغير المجتمع  ومتطلباته تغيرت الأدوار فأصبح غياب دور الأب جليا في التنشئة الأسرية وهذا ما يؤدي الى سوء توافق الأبناء وانحرافهم خاصة إذا كانوا في فترة حرجة وحساسة كفترة المراهقة، وعلى هذا الأساس قمنا بدراسة هدفها التحقق من تأثير صورة الأب على ظهور السلوك الجانح لدى المراهق، وقد أجرينا دراستنا بمركز إعادة التربية "قالمة" معتمدين على المنهج الإكلينيكي مستخدمين دراسة الحالة على عينة من الأحداث الجانحين، كما اعتمدنا على المقابلة نصف الموجهة واختبار تفهم الموضوع . وقد تمثلت النتائج في أن لصورة الأب علاقة بظهور السلوك الجانح لدى المراهق (نمط الأب المهمل، المتسلط)، فالإهمال العاطفي يفقد المراهق ثقته بنفسه وهذا ما يدفعه الى العدوان كحل لإثبات ذاته وتأكيد قوته. The family has an important function in society and it represented in the creation of children and instilling moral values and benign virtues in them, this is what it translates through integrate the roles of their members among themselves especially parents, however with the change of society and its requirement roles have changed, so the absence of the father’s role becomes evident in family development and this leads to the poor compatibility of children and their deviation, especially if they are in critical and sensitive period as the period of adolescence. On this basis we studied our goal and verified the effect of the father’s image on the appearance of delinquent behavior in the adolescent we conducted the study on the rehabilitation center “guelma” based on the clinical approach using a case study on a sample of the delinquent events, we also relied on a semi-directed interview and a test of understanding of the subject. The result is that the image of the father is related to the appearance of delinquent behavior in the adolescent (the style of the neglected father, or domineering) emotional neglect loses the teenager’s self confidence and this is what leads him to aggression as a solution to prove himself and confirm his strength.